2020
DOI: 10.3390/plants9030394
|View full text |Cite
|
Sign up to set email alerts
|

Ecological and Landscape Factors Affecting the Spread of European Mistletoe (Viscum album L.) in Urban Areas (A Case Study of the Kaliningrad City, Russia)

Abstract: Green spaces are very important for an urban environment. Trees in cities develop under more stressful conditions and are, therefore, more susceptible to parasite including mistletoe infestation. The aim of this study was to investigate the ecological, microclimatic, and landscape factors causing the spread of European mistletoe (Viscum album L.) in urban conditions. The most numerous hosts of mistletoe were Tilia cordata (24.4%), Acer platanoides (22.7%), and Populus nigra (16.7%). On average, there were more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 35 publications
0
14
0
3
Order By: Relevance
“…An increase in the abundance of mistletoe is associated with planting of parks or parkways with suitable hosts and good light conditions for single or loosely planted trees; it may also be important to note that the urban area has many locations conducive to birds that may spread mistletoe 64 , 65 . Thus, the conditions for growth and spreading in urban conditions are very good, especially since mistletoe is very resistant to air pollution 66 , 67 . Viscum album subsp.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in the abundance of mistletoe is associated with planting of parks or parkways with suitable hosts and good light conditions for single or loosely planted trees; it may also be important to note that the urban area has many locations conducive to birds that may spread mistletoe 64 , 65 . Thus, the conditions for growth and spreading in urban conditions are very good, especially since mistletoe is very resistant to air pollution 66 , 67 . Viscum album subsp.…”
Section: Discussionmentioning
confidence: 99%
“…This tree species was selected as it is more susceptible to European mistletoe infestation ( Viscum album L. subsp. Album ) in Kaliningrad [ 8 ]. The trees under study were located on a test plot of approximately 250 m × 250 m, situated in the territory of Kaliningrad (54°44′56″ N, 20°30′55″ E).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies [ 8 ] showed that in the territory of Kaliningrad, the trees of the small-leaved linden ( Tilia cordata Mill.) are more susceptible to mistletoe infestation compared to other urban trees.…”
Section: Introductionmentioning
confidence: 99%
“…abietis on fir (Plagnat 1950;Zuber 2004;Szmidla et al 2019). This hemiparasite is indicated in Poland by crown thinning and death of Scots pine trees during drought, most often in older stands The intense occurrence of mistletoe also limits the activity of mycorrhizal roots by a shortening carbohydrates supply from dying tree crowns, worsening its water balance and accelerating drought symptoms (Barbu 2010;Szmidla et al 2019;Billigly et al 2018;Skrypnik et al 2020). Gehring and Whitham (1991) found a significant impact of Juniperus mistletoe (Phoradendron juniperinum Engelm.)…”
Section: Phytopathogens and Entomopathogens Under Droughtmentioning
confidence: 99%